Effects of steam explosion on the nutritional and functional properties of black‐grained wheat bran and its application. (8th January 2023) - Liu, Yuxiu; Huang, Shuhua; Meng, Tianqi; Wang, Yizhao; Zhang, Zhengmao
Abstract: Background: In recent years, an increasing interest in healthy functional foods has been documented among health‐conscious consumers. Steam explosion (SE)‐treated black‐grained wheat (BGW) bran was explored for the development of chiffon cakes with high nutritional and functional value. Results: The content of crude fat and total starch decreased with increasing SE pressure, whereas water‐holding capacity and antioxidant activity increased, suggesting SE at 0.6–1.0 MPa could be an effective technique for enhancing the nutritional and functional properties of wheat bran. The protein, iron, zinc, manganese, selenium, and soluble dietary fiber contents, the water‐holding, oil‐binding, swelling, cholesterol binding, and cation‐exchange capacities, and antioxidant activity of SE BGW bran were better than those of SE white‐grained wheat bran. The addition of SE bran (0.8 MPa) to flour significantly decreased the peak viscosity, final viscosity, and setback and increased the pasting temperature. The effect of SE bran on the pasting properties of low‐gluten and medium‐gluten flour was stronger than that of high‐gluten flour. SE BGW bran altered the physicochemical properties of chiffon cakes. When 6% SE BGW bran (0.8 MPa) was added, chiffon cakes exhibited good specific volume, hardness, chewiness, and other sensory qualities. Conclusions: These results indicate that SE at 0.6–1.0 MPa is an effective technique for enhancing the nutritional and functional properties of wheat bran. SE BGW bran can be alternatives to food materials for developing health functional cereal‐based products. © 2022 Society of Chemical Industry.